Applying the Theory of the Planned Behavior on Halal Logistics Services Adoption among Food & Beverages Small and Medium Enterprises - Norlila Mahidin; Mastora Mustafar; Ezanee Mohamed Elias; Siti Zakiah Abu Bakar (International Journal of Supply Chain Management, 2019)
The objective of the study is to determine the main behavior affecting the adoption of halal food logistics (HFL) services among the SMEs - food and beverages manufacturers in Malaysia. Presently, the demand for halal products by Muslim consumers has increased exponentially as well as the concerned on the transportation services status. Thus, the existing of the HFL is designed especially to meet the demand from halal manufacturers to maintain the integrity of their halal products along the supply chain. Unfortunately, the demand of these services among the SMEs are moderately small. Based on TPB model, the study utilize survey questionnaires to obtain data from 596 respondents from listed database. The useful questionnaires which are 128 responses were analyzed by SPSS and the Smart SEM-PLS. From the analysis, subjective norms were found to have a significant relationship with an intention to adopt the HFL services but variables of attitude and perceived behavior control are not significant. The results has provided an understandings on the behavioural among these SMEs to adopt HFL services in Malaysia. In this context, the HFL services can be a part of a business strategies in protecting the halal integrity either from perspective of manufacturers, logistics providers towards the consumers’ needs. The implication, limitation and suggestion for the future study are also be discussed in the conclusion paragraph.